A single dose of exercise stimulates skeletal muscle mitochondrial plasticity in myotonic dystrophy type 1. (10th February 2023) - Mikhail, Andrew I.; Manta, Alexander; Ng, Sean Y.; Osborne, Aislin K.; Mattina, Stephanie R.; Mackie, Mark R.; Ljubicic, Vladimir
Abstract: Aim: Myotonic dystrophy type 1 (DM1) is the second most common muscular dystrophy after Duchenne and is the most prevalent muscular dystrophy in adults. DM1 patients that participate in aerobic exercise training experience several physiological benefits concomitant with improved muscle mitochondrial function without alterations in typical DM1‐specific disease mechanisms, which suggests that correcting organelle health is key to ameliorate the DM1 pathology. However, our understanding of the molecular mechanisms of mitochondrial turnover and dynamics in DM1 skeletal muscle is lacking. Methods: Skeletal muscle tissue was sampled from healthy and DM1 mice under sedentary conditions and at several recovery time points following an exhaustive treadmill run. Results: We demonstrate that DM1 patients exhibit an imbalance in the transcriptional apparatus for mitochondrial turnover and dynamics in skeletal muscle. Additionally, DM1 mice displayed elevated expression of autophagy and mitophagy regulators. A single dose of exercise successfully enhanced canonical exercise molecular pathways and skeletal muscle mitochondrial biogenesis despite failing to alter the cellular pathology in DM1 mice. However, treadmill running stimulated coordinated organelle fusion and fission signaling, as well as improved alternative splicing of Optic atrophy 1 . Exercise also evoked autophagy and mitophagy pathways in DM1 skeletal muscle resulting in the normalized expression of autophagy‐ and lysosome‐related machinery responsible for the clearance of dysfunctional organelles. Conclusion: Collectively, our data indicate that mitochondrial dynamics and turnover processes in DM1 skeletal muscle are initiated with a single dose of exercise, which may underlie the adaptive benefits previously documented in DM1 mice and patients.